2008
DOI: 10.1007/s00216-008-2070-4
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive HPLC–fluorescence detection of morphine labeled with DIB-Cl in rat brain and blood microdialysates and its application to the preliminarily study of the pharmacokinetic interaction between morphine and diclofenac

Abstract: microdialysates at a signal-to-noise ratio of 3 were 0.4 and 0.6 ng/ml, respectively. The proposed method was successfully applied to preliminarily study of potential pharmacokinetic interaction of Mor with diclofenac.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

7
2

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 26 publications
(40 reference statements)
0
9
0
Order By: Relevance
“…The in vivo recoveries of the dialysis probe (R in vitro ) were calculated from four replicate measurements of in vitro recoveries (R in vitro ), in vitro losses (L in vitro ), and in vivo losses (L in vivo ), according to previous reports (Sun et al, 2002;Wada et al, 2008 …”
Section: In Vivo Brain Microdialysismentioning
confidence: 99%
“…The in vivo recoveries of the dialysis probe (R in vitro ) were calculated from four replicate measurements of in vitro recoveries (R in vitro ), in vitro losses (L in vitro ), and in vivo losses (L in vivo ), according to previous reports (Sun et al, 2002;Wada et al, 2008 …”
Section: In Vivo Brain Microdialysismentioning
confidence: 99%
“…In our study, the combination of HPLC separation with fluorescence detection using our original labeling reagent (DIBCl) and microdialysis sampling were used for estimation for drug-drug interactions of abusable drugs. 58,[70][71][72] MDMA tablets often contain other active components having hallucinogenic and/or stimulant effect such as caffeine, ketamine, ephedrine or methamphetamine. After administration of MDMA (5 mg/kg, i.p.)…”
Section: ·2 Evaluation Of Drug-drug Interaction Potential Formentioning
confidence: 99%
“…These results suggested that the clinical benefit of combined use of Mor and Dic might be caused by synergism of their different pharmacodynamic effects and/or by pharmacokinetic effects of Mor glucuronide. 58 Appetite suppressants have been used as Phen-Fen combinations; however, such use was found to enhance weight loss at lower doses as well as the neurotoxic effect. The profiles of pharmacokinetic parameters of Phen in rats, both blood and brain, following Phen (1 or 5 mg/kg) in the absence or presence of Fen (1 or 5 mg/kg) were significantly altered.…”
Section: ·2 Evaluation Of Drug-drug Interaction Potential Formentioning
confidence: 99%
“…For safety precautions, sensitive monitoring of MO in blood or urine is necessary. Several methods have been developed for the detection and determination of MO, including sequential injection analysis method [13], cation-selective exhaustive injection and sweeping micellar electrokinetic chromatography [14], fast Fourier transformation with continuous cyclic voltammetry method [15], gas chromatography -mass spectrometry [16], high-performance liquid chromatography -fluorescence method [17], liquid chromatography -electrospray ionization ion trap mass spectrometry [18], and microchip method [19]. However, these analytical methods are time-consuming and devices are expensive.…”
Section: Introductionmentioning
confidence: 99%